Basal serum luteinising hormone cut-off, and its utility and cost-effectiveness for aiding the diagnosis of the onset of puberty in girls with early stages of breast development - Somboon Wankanit (2020)
© 2019 John Wiley & Sons Ltd Objective: To determine basal and gonadotrophin-releasing hormone analogue (GnRHa)-stimulated peak luteinising hormone (LH) cut-offs to diagnose onset of early or normal puberty in girls with each Tanner stage of breast (II and III). Design, Patients and Measurements: A retrospective study of 601 girls with breast onset before 8 years of age who underwent GnRHa test was conducted. Patients were categorized as CPP and premature thelarche. Each group was divided into two subgroups; Tanner II and III. Cost-effectiveness analysis was performed. Results: In comparison with basal LH cut-off of 0.3 IU/L, basal LH cut-off of 0.2 IU/L had comparable specificity (Tanner II: 98.0% vs 94.8%, Tanner III: 98.8% vs 93.8%), but greater sensitivity (Tanner II: 28.3% vs 41.7%, Tanner III: 45.2% vs 59.3%). Specificity of basal LH cut-off of 0.2 IU/L was not inferior to that of the traditionally used peak LH of 5 IU/L. Using basal LH cut-off of 0.2 IU/L followed by GnRHa test in girls with negative basal LH was more cost-saving when compared with using the cut-off of 0.3 IU/L. Moreover, using basal LH cut-off of 0.2 IU/L followed by GnRHa test provided a cost reduction when compared with performing GnRHa test in all patients. Conclusions: Basal serum LH cut-off of 0.2 IU/L could be a simple and cost-saving tool for initial diagnosis of onset of early or normal puberty in girls with Tanner II and III before proceeding to GnRH testing.